20 Cross-Reactivity Between Olive Pollen and 3 Species of Grasses in Madrid, Spain - Fernandez-Caldas, Enrique (World Allergy Organization Journal, 2012)
BACKGROUND: The most common allergenic pollens in patients with pollinosis in Central Spain are grasses and olive pollen, with a prevalence of positive skin prick test results of 94 and 61%, respectively. Shared proteins have been described in olive and grasses, such as profilins, polcalcin and trypsin inhibitors, but there are few in vitro studies analyzing the potential cross reactivity between both species. The aim of the present study was to analyze the protein composition of both allergen extracts, and the allergenic cross-reactivity between O. europaea and different grass pollen species. METHODS: Seventy-two (72) patients (mean age 10.4 years) were included in the study. All of them suffered rhinoconjuntivitis and/or asthma and were sensitized to olive and/or grass pollen. Specific IgE of the individual patients against O. europaea, and to the grass species: Dactylis glomerata, Phleum pratense and Trisetum paniceum were determined by ELISA. Inhibition assays were performed to verify allergenic crossreactivity between grass species and olive. Mass spectrometry analysis was performed to characterize the extracts and establish if there are common proteins in both, grass and olive pollens, that could act as cross reactive proteins. RESULTS: Three different sensitization patterns were observed: 1) sensitization to olive and grass pollen, 2) sensitization to olive and not to grasses and 3) sensitization to grasses and not to olive. Different pools of sera were mixed according to this classification and used for the different assays. Correlation coefficients found for the 3 grass species were significant (P < 0.0001; Spearman), but not for olive pollen (P = 0.14; Spearman). Proteomic analysis revealed the presence of more than 40 common proteins in grasses and olive pollens, but inhibition assays demonstrated no allergenic cross-reactivity between both families. CONCLUSIONS: There is no in vitro crossreactivity between O. europaea and Grass pollen extracts, in spite of the allergens and the large number of common proteins shared by these pollens. We can conclude that sensitization to olive and grasses is species specific.